2019
DOI: 10.1136/injuryprev-2018-042982
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and economic burden of fall-related injuries in older Chinese people: a systematic review

Abstract: ObjectiveChina’s population is ageing and fall-related injury in older Chinese people is a growing public health concern. This review aims to synthesise existing evidence on the incidence, risk factors and economic burden of fall-related injury among older Chinese people to inform health service planning.MethodsA systematic search of literature on falls and injury among older people living in China was performed in six electronic databases including both English and Chinese databases. Results were combined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 45 publications
2
61
1
2
Order By: Relevance
“…Results relating to gender have proved inconsistent. In their study on community-dwelling older adults, Zhao et al [37] reported that men were more likely to fall than women, as in our results, but another study reported that women were more likely to fall than men mainly in community-dwelling setting [38]. Further research is needed to investigate the association between falls and gender in hospitals.…”
Section: Discussionsupporting
confidence: 54%
“…Results relating to gender have proved inconsistent. In their study on community-dwelling older adults, Zhao et al [37] reported that men were more likely to fall than women, as in our results, but another study reported that women were more likely to fall than men mainly in community-dwelling setting [38]. Further research is needed to investigate the association between falls and gender in hospitals.…”
Section: Discussionsupporting
confidence: 54%
“…The most likely reason is that elderly female Chinese have been reported to have a high risk of falls. 40 That is, when assessing female VCI subjects, fall prevention should be evaluated carefully. A comparison of the care bundles in the patients with AD or VCI is listed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…Falls occur as a result of a complex interaction of risk factors [ 3 ]. The associated risk factors include advanced age [ 4 ], muscle weakness [ 5 , 6 ], gait disorders [ 7 ], balance impairment [ 8 ], cognitive deficits [ 9 ], and others. In terms of intervention effect or time and energy consumption, active exercise is the best way to prevent falls among the elderly [ 10 ].…”
Section: Introductionmentioning
confidence: 99%